2023
DOI: 10.3390/app13031340
|View full text |Cite
|
Sign up to set email alerts
|

Explore Long-Range Context Features for Speaker Verification

Abstract: Multi-scale context information, especially long-range dependency, has shown to be beneficial for speaker verification (SV) tasks. In this paper, we propose three methods to systematically explore long-range context SV feature extraction based on ResNet and analyze their complementarity. Firstly, the Hierarchical-split block (HS-block) is introduced to enlarge the receptive fields (RFs) and extract long-range context information over the feature maps of a single layer, where the multi-channel feature maps are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The back-end scoring method then measures the similarity of linguistic representations to determine the language to which the utterance belongs. Recently, numerous studies have shown that an end-to-end approach has integrated these two stages into a single neural module [14][15][16][17][18]. A good language embedding extractor is crucial for robust and high-performance LID systems.…”
Section: Introductionmentioning
confidence: 99%
“…The back-end scoring method then measures the similarity of linguistic representations to determine the language to which the utterance belongs. Recently, numerous studies have shown that an end-to-end approach has integrated these two stages into a single neural module [14][15][16][17][18]. A good language embedding extractor is crucial for robust and high-performance LID systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the temptation to assert linear sequence models as superior, properly testing for information retention from long-context tasks remains callenging. While some works have attempted to evaluate this ability through long contexts (Shaham et al, 2022;Pang et al, 2022;Dong et al, 2024;Bai et al, 2023;Li et al, 2023;Han et al, 2024), whether or not they truly require the use of long-contexts is uncertain and ascertaining long-context abilities from these tasks is difficult. This has prompted the use of more synthetic tasks (Hsieh et al, 2024), such as needle-ina-haystack (NIAH) (Kamradt, 2023) and passkey retreival (Mohtashami and Jaggi, 2023), to better control and evaluate the context sizes of models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hsieh et al (2024) claim modern LLMs significantly over-state true context windows on a number of synthetic tasks. Meanwhile Han et al (2024) observe models to perform reasonably well on synthetic tasks, but struggle on real-world tasks, as do Li et al (2023). Hence despite a consistent trend in models behaving underwhelmingly, it remains to be understood why this occurs.…”
Section: Introductionmentioning
confidence: 99%